Dependence of quartz wettability on fluid density - Al-Yaseri, A.; Roshan, H.; Lebedev, M.; Barifcani, A.; Iglauer, Stefan (American Geophysical Union, 2016)
Wettability is one of the most important parameters in multiphase flow through porous rocks. However, experimental measurements or theoretical predictions are difficult and open to large uncertainty. In this work we demonstrate that gas densities (which are much simpler to determine than wettability and typically well known) correlate remarkably well with wettability. This insight can significantly improve wettability predictions, thus derisking subsurface operations (e.g., CO2 geostorage or hydrocarbon recovery), and significantly enhance fundamental understanding of natural geological processes.